Feasibility study of using vegetable oil as a cutting lubricant through the use of minimum quantity lubricant during machining - Sharif, Safian; Mohd. Yusof, Noordin; Idris, Mohd. Hasbullah; Ahmad, Zainal Abidin; Sudin, Izman; Ripin, Adnan; Mat Zin, Azrul Hisyam (Faculty of Mechanical Engineering, 2009)
In machining, the occurrence of tool wear is a natural phenomenon which may lead to tool failure. The deformation during cutting at the interface between the tool face and workpiece tends to generate high cutting temperature. This condition reduces the tool life and the surface quality of the workpiece. The application of flood coolant to reduce the friction at the tool-workpiece may create several environmental problems. The introduction of Minimum Quantity Lubrication (MQL) as an alternative technique which is the process of pulverizing a very small amount of oil (< 30ml/h) can be regarded as replacement of dry machining while it may also be considered as an alternative to flood cooling. The research focused on the feasibility of using palm oil as cutting lubricant through the use of MQL during end milling hardened STAVAX ESR stainless steel of hardness 50 HRC with TiAlN and AlTiN coated carbide tools. The effect of various kind of lubricant and cutting speed on tool life, tool wear, cutting forces and surface integrity. The application of this ‘green machining’ would improve the plant environment, reduce the pollution, minimize the industrial hazard, reduce the machining cost and prolonged the tool life.